A Review of Microwave Synthesis of Zinc Oxide Nanomaterials: Reactants, Process Parameters and Morphologies - Jacek Wojnarowicz; Tadeusz Chudoba; Witold Lojkowski (Nanomaterials, 2020)
Zinc oxide (ZnO) is a multifunctional material due to its exceptional physicochemical properties and broad usefulness. The special properties resulting from the reduction of the material size from the macro scale to the nano scale has made the application of ZnO nanomaterials (ZnO NMs) more popular in numerous consumer products. In recent years, particular attention has been drawn to the development of various methods of ZnO NMs synthesis, which above all meet the requirements of the green chemistry approach. The application of the microwave heating technology when obtaining ZnO NMs enables the development of new methods of syntheses, which are characterised by, among others, the possibility to control the properties, repeatability, reproducibility, short synthesis duration, low price, purity, and fulfilment of the eco-friendly approach criterion. The dynamic development of materials engineering is the reason why it is necessary to obtain ZnO NMs with strictly defined properties. The present review aims to discuss the state of the art regarding the microwave synthesis of undoped and doped ZnO NMs. The first part of the review presents the properties of ZnO and new applications of ZnO NMs. Subsequently, the properties of microwave heating are discussed and compared with conventional heating and areas of application are presented. The final part of the paper presents reactants, parameters of processes, and the morphology of products, with a division of the microwave synthesis of ZnO NMs into three primary groups, namely hydrothermal, solvothermal, and hybrid methods.